Semiotics of Buang-buang Ae’ Tradition; Relationship Between Humans, Modern Medicine and Islam on Coastal Communities in Dabong Kubu Raya West Kalimantan - Abong, Rustam; Hakim, Muhammad Luthfy; Darmadi, Didi (Khatulistiwa, 2018)
This study aims to reveal the relationship between humans and nature. Researchers used data from Buang-buang Ae’ tradition discussed in terms of semiotics to see Buang-buang Ae’ Tradition': Relationship Between Humans, Modern Medicine, and Islam in Coastal Communities in Dabong, Kubu Raya, West Kalimantan. Data obtained from the field shows that: 1. A waste of tradition is aimed at treatment, facilitating the birth process so that it is not difficult (difficult) and so that it is not disturbed by spirits. Although now there is community who do not believe anymore, they are still only carried out as a condition or formality. 2. The semiotic of Buang-buang Ae’ tradition is a myth that describes human relationships with nature and the creator that takes place in balance and moderation. 3. From modern medicine, the community has been able to accept the presence of midwives as partners of traditional birth attendants in the labor process for Dabon people, because both of them aim to save the lives of those who want to give birth and their babies. The Prophet Khaidir is considered as a horizontal and vertical axis because the water ruler represents Allah. So that with the tradition of Buang-buang ae' is considered capable of connecting ordinary people with Prophet Khaidir. Moreover, in the pronunciation of word ‘mantra’, there is a sentence of ‘Assalamu ‘alaikum, Prophet Khaidir’ and ‘Bismillahirrahmanirrahim’, which proves Islamization by previous preachers, known as Sufistic Islam or Muslim moderation. There are some informants who argue that the tradition of Buang-buang ae’ contains syirk, but it is limited to the implementation of this tradition.